PENGARUH PLUGGING TERHADAP PERHITUNGAN EFEKTIVITAS HEATER di PLTU Suralaya - , ANTONIUS ADI HENDRA SAPUTRA; , Ir. Soeadgihardo S., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Heater is a heat exchanger which function to heat a fluid by providing heat from high temperature steam to fluid which has a lower temperature. In Suralayaâs Steam Power Plant, heater has function to preheating on feedwater that will go to the boiler. There are some major trouble in heater such as leakages and blockages which may affect the effectiveness of the heater. Calculation the value of the effectiveness of the heater can be done by using the formula Ì Ì so the calculation of the effectiveness of the heater can be known and can also be seen what factors which influence the value of the effectiveness based on the formula and of the effectiveness also we can conclude that the heater is still in good condition or not. Of the heaters effectiveness calculation showed that the value of the effectiveness of the heaters are 88,2% and 90%, based on the value of the effectiveness it can be concluded that the heater is still in good condition. And to maintain and even to improve the effectiveness can be done by continuing to maintenance on the heater so that blockages or leaks do not happen again.